The birdcage - Nichols, Mike.; May, Elaine, 1932-; Poiret, Jean, 1926-1992.; Williams, Robin, 1951-2014; Lane, Nathan, 1956-; Hackman, Gene.; Wiest, Dianne; Baranski, Christine; United Artists Corporation; MGM/UA Home Video (Firm) (Santa Monica, Calif. : MGM/UA Home Video, 2005)
The story of a middle-aged gay couple's comic encounter with a self-righteously straight and conservative family: Armand and Albert reluctantly accept young Val's intention to marry the daughter of a conservative Senator, but when the fiancee's family comes to visit, the whole household is turned upside down.
Based on the stage play La Cage aux folles by Jean Poiret and the motion picture La Cage aux folles, directed by Francis Veber.
Executive producers, Neil Machlis, Marcello Danon ; director of photography, Emmanuel Lubezki.
Robin Williams, Nathan Lane, Gene Hackman, Dianne Wiest, Dan Futterman, Calista Flockhart, Hank Azaria, Christine Baranski.
Rated R.
DVD.
English, French and Spanish language tracks; English, French and Spanish subtitles; closed captioned.
Keywords: Gay couples -- Florida -- Miami Beach -- Drama; Fathers and sons -- Florida -- Miami Beach -- Drama; Films for the hearing impaired